Communication network actors in Celempungan and Seren Taun attractions in tourism village - Siregar, Mariana Rista Ananda; Nugraha, Yogprasta Adi; Kartika, Mutiara (Jurnal Studi Komunikasi, 2025)
Ciasmara Village in Bogor Regency offers cultural attractions like Celempungan music and the Seren Taun ritual, which are valuable assets within a Community-Based Tourism (CBT) model. This study analysed the communication network managing these events, emphasising the identification and role of central actors in local tourism governance. Using a descriptive quantitative approach and social network analysis, data were collected from 21 appointed tourism managers. UCINET VI software was employed to measure degree, closeness, betweenness, and eigenvector centrality. Results show that actor centrality significantly shapes the effectiveness of the CBT network. Otang Celempung emerged as the most central figure, actively facilitating communication and decision-making. Uday, acting as a liaison, connects otherwise separate groups. The findings highlight the need to strengthen the capacity of key actors to foster collaboration, preserve cultural heritage, and promote sustainable rural tourism.